Unique case of oligoastrocytoma with recurrence and grade progression: Exhibiting differential expression of high mobility group-A1 and human telomerase reverse transcriptase - Gandhi, Puneet (World J Clin Cases, 2016)
Mixed gliomas, primarily oligoastrocytomas, account for about 5%-10% of all gliomas. Distinguishing oligoastrocytoma based on histological features alone has limitations in predicting the exact biological behavior, necessitating ancillary markers for greater specificity. In this case report, human telomerase reverse transcriptase (hTERT) and high mobility group-A1 (HMGA1); markers of proliferation and stemness, have been quantitatively analyzed in formalin-fixed paraffin-embedded tissue samples of a 34 years old patient with oligoastrocytoma. Customized florescence-based immunohistochemistry protocol with enhanced sensitivity and specificity is used in the study. The patient presented with a history of generalized seizures and his magnetic resonance imaging scans revealed infiltrative ill-defined mass lesion with calcified foci within the left frontal white matter, suggestive of glioma. He was surgically treated at our center for four consecutive clinical events. Histopathologically, the tumor was identified as oligoastrocytoma-grade II followed by two recurrence events and final progression to grade III. Overall survival of the patient without adjuvant therapy was more than 9 years. Glial fibrillary acidic protein, p53, Ki-67, nuclear atypia index, pre-operative neutrophil-lymphocyte ratio, are the other parameters assessed. Findings suggest that hTERT and HMGA1 are linked to tumor recurrence and progression. Established markers can assist in defining precise histopathological grade in conjuction with conventional markers in clinical setup.